Improved Coding of Postoperative Deep Vein Thrombosis and Pulmonary Embolism in Administrative Data (AHRQ Patient Safety Indicator 12) After Introduction of New ICD-9-CM Diagnosis Codes. Issue 5 (May 2015) - Sadeghi, Banafsheh; White, Richard H.; Maynard, Gregory; Zrelak, Patricia; Strater, Amy; Hensley, Laurie; Cerese, Julie; Romano, Patrick
Abstract : Background: Symptomatic venous thromboembolism is a common postoperative complication. The Agency for Healthcare Research and Quality (AHRQ) has developed a Patient Safety Indicator 12 to assist hospitals, payers, and other stakeholders to identify patients who experienced this complication. Objectives: To determine whether newly created and recently redefined ICD-9-CM codes improved the criterion validity of Patient Safety Indicator 12, based on new samples of records dated after October 2009. Research Design, Subjects, Measures: Two sources of data were used: (1) UHC retrospective case-control study of risk factors for acute symptomatic venous thromboembolism occurring within 90 days after total knee arthroplasty in teaching hospitals; (2) chart abstraction data by volunteer hospitals participating in the Validation Pilot Project of the AHRQ. Results: In the UHC sample, the positive predictive value (PPV) was 99% (125/126) and the negative predictive value was 99.4% (460/463). In the AHRQ sample, the overall PPV was 81% (126/156). Conclusions: The PPV based on both samples shows substantial improvement compared with the previously reported PPVs of 43%–48%, suggesting that changes in ICD-9-CM code architecture and better coding guidance can improve the usefulness of coded data. Abstract : Supplemental Digital Content is available in the text.